Turkey as a donor country and potential partner in triangular cooperation - Jeannine Hausmann (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Turkey has developed into a significant donor country within international development cooperation over the last few years. This paper outlines the goals and principles of Turkish development cooperation and analyses their significance for the country's foreign policy. It takes a closer look at the scope of services and key actors within Turkish development policy, the geographic and sectoral priorities of development cooperation, and the main procedures used, before lastly examining the question of a potential partnership between Turkey and Germany in a triangular cooperation context.
Keywords: 330; Aufstrebende Mächte; Deutsche + Europäische + multilaterale Entwicklungspolitik